Đơn giản hộ em biểu thức: `[(3(x+2))/(2(x^3+ x^2 + x + 1)) + (2x^2 – x -10)/(2(x^3 – x^2 + x -1))] : [5/(x^2 + 1) + 3/(2(x+1)) – 3/ (2 (x-1))]`

Question

Đơn giản hộ em biểu thức:
`[(3(x+2))/(2(x^3+ x^2 + x + 1)) + (2x^2 – x -10)/(2(x^3 – x^2 + x -1))] : [5/(x^2 + 1) + 3/(2(x+1)) – 3/ (2 (x-1))]`

in progress 0
Rylee 3 tháng 2021-09-17T06:01:37+00:00 1 Answers 5 views 0

Answers ( )

    0
    2021-09-17T06:03:10+00:00

    Giải thích các bước giải:

     Biểu thức trên có dạng `A= B:C`

    `B = [(3(x+2))/ (2(x^2 + 1)(x+1)) + ((x+2)(2x-5))/(2(x^2)(x-1))]`

    `= ((x-2)[3(x-1) + (x-1)(2x-5)]/(2(x^2+1)(x+1)(x-1)`

    `= ((x+2)(2x^2 -8))/(2(x^2+1)(x-1)(x+1))`

    `C = [5/(x^2 +1) + 3/(2(x+1)) – 3/(2(x-1))]`

    `= (10(x-1)(x+1)+3(x-1)(x^2+1)-3(x+1)(x^2 +1))/(2(x^2+1)(x+1)(x-1))`

    `= (4x^2 – 16)/(2(x^2+1)(x+1)(x-1))`

    `A= B:C = ((x+2)2(x^2-4))/(2(x^2 + 1)(x+1)(x-1)) : (4(x^2 – 4))/ (2(x^2 +1)(x+1)(x-1))`

    `= (x+2)/2`

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )